(untitled) (Journal of Geography and Environmental Management, 2018)
In article the major anthropogenic factors, defining spatial distribution and dynamics of negative processes of a morphogenesis within a platform-denudational plains of the Central Kazakhstan which are characterized by aridity of climatic conditions are considered. Changes of processes of a morphogenesis and components of the environment is defined by type (engineering and economic, mining and mining processing industries, agricultural, town-planning, etc.) and character (direct and mediated) economic influence. The lands broken by economic activity occupy the huge spaces, catastrophically reducing territories of the equipped vital space of the population of the Central Kazakhstan.